2021
DOI: 10.1002/pbc.28957
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and risk factors for venous thromboembolism in adolescent and young adult oncology patients

Abstract: Background Venous thromboembolism (VTE) is a known complication among pediatric and adult cancer patients. Adolescent and young adult oncology (AYAO) patients have unique biological and physiological characteristics that make them distinct from other populations. Our objective was to study the VTE incidence, risk factors, and outcomes, which have been understudied in this population. Procedure A retrospective case–control study was conducted on AYAO participants with new or relapsed cancer and an imaging confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Since the risk of some complications might be higher during treatment (i.e., intensive use of CVC), the IRs per 1000 CVC-treatment days were also calculated, which still showed that the insertion of a SL PICC is associated with a significantly higher risk of (severe) complications and local infections in particular compared to a TIVAP. The high rate of complications associated with PICCs was also reported previously in adult patients with HL and pediatric oncology patients in general [1,[9][10][11][12][13]. Three studies did investigate risk factors for CVT (CVC and non-CVCrelated) specifically in pediatric patients with lymphoma.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Since the risk of some complications might be higher during treatment (i.e., intensive use of CVC), the IRs per 1000 CVC-treatment days were also calculated, which still showed that the insertion of a SL PICC is associated with a significantly higher risk of (severe) complications and local infections in particular compared to a TIVAP. The high rate of complications associated with PICCs was also reported previously in adult patients with HL and pediatric oncology patients in general [1,[9][10][11][12][13]. Three studies did investigate risk factors for CVT (CVC and non-CVCrelated) specifically in pediatric patients with lymphoma.…”
Section: Discussionsupporting
confidence: 54%
“…This incidence falls within the wide range reported for children with cancer in general of 2–50% [ 27 29 ]. The risk of CVC-related CVTs has been described to be higher in patients with HL compared to other oncology patients, presumably caused by the frequent presence of risk factors for CVT (e.g., vein compression in the upper body, high-dose corticosteroid treatment), as also described in the “Introduction” section [ 1 , 3 , 9 , 11 14 , 28 ]. However, the difference between HL and non-HL patients might also be explained by the CVC types included in the previously performed studies, i.e., only 0–3% PICCs [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations